Produktivitas Kerja Dosen Dipengaruhi Kompetensi, Motivasi dan Pengalaman Kerja - Muh. Fahrurrozi; Hary Murcahyanto; Mohzana Mohzana (Alignment:Journal of Administration and Educational Management, 2021)
This study aims to identify the effect of competence, motivation and work experience on the work productivity of lecturers at the Faculty of Social Sciences and Economics, Hamzanwadi University, East Lombok, either partially or simultaneously. Using a quantitative approach with a correlational method to ascertain whether there is a bond between 2 or more variables. The population, all lecturers of the Faculty of Social Sciences and Economics, totaling 32 lecturers. The sampling method utilizes saturated sampling method. Information analysis procedures use descriptive information, information analysis prerequisite test, hypothesis testing. Information analysis of the influence of competence, motivation and work experience on lecturers' work productivity is processed using SPSS16. 0 for windows. The results of the t-test research show that each independent variable, namely competence and work motivation, partially affects positively and significantly, whereas work experience partially does not affect work productivity. The results of the F test research 70% of work productivity is influenced by aspects of competence, motivation and work experience, on the other hand the remaining 30% is described or predicted by other aspects outside the three aspects and other models outside the model. The conclusion is partially that the competence variable is more influential than the motivation and work experience variables on work productivity, but simultaneously the competence, motivation and work experience variables affect the lecturer's work productivity Keywords: Work Productivity, Work Motivation, Work Experience